Psychological, physical, and sleep comorbidities and functional impairment in irritable bowel syndrome: Results from a national survey of U.S. adults. - Madhusudan Grover; Bhanu Prakash Kolla; Rahul Pamarthy; Meghna P Mansukhani; Margaret Breen-Lyles; Jian-Ping He; Kathleen R Merikangas (PLoS ONE)
Background/aims Patients with irritable bowel syndrome (IBS) in referral practice commonly report mental disorders and functional impairment. Our aim was to determine the prevalence of mental, physical and sleep-related comorbidities in a nationally representative sample of IBS patients and their impact on functional impairment. Methods IBS was defined by modified Rome Criteria based on responses to the chronic conditions section of the National Comorbidity Survey-Replication. Associations between IBS and mental, physical and sleep disorders and 30-day functional impairment were examined using logistic regression models. Results Of 5,650 eligible responders, 186 met criteria for IBS {weighted prevalence 2.5% (SE = 0.3)}. Age >60 years was associated with decreased odds (OR = 0.3; 95% CI:.1-.6); low family income (OR = 2.4; 95% CI:1.2-4.9) and unemployed status (OR = 2.3; 95% CI:1.2-4.2) were associated with increased odds of IBS. IBS was significantly associated with anxiety, behavior, mood disorders (ORs 1.8-2.4), but not eating or substance use disorders. Among physical conditions, IBS was associated with increased odds of headache, chronic pain, diabetes mellitus and both insomnia and hypersomnolence related symptoms (ORs 1.9-4.0). While the association between IBS and patients' role impairment persisted after adjusting for mental disorders (OR = 2.4, 95% CI 1.5-3.7), associations with impairment in self-care, cognition, and social interaction in unadjusted models (ORs 2.5-4.2) were no longer significant after adjustment for mental disorders. Conclusion IBS is associated with socioeconomic disadvantage, comorbidity with mood, anxiety and sleep disorders, and role impairment. Other aspects of functional impairment appear to be moderated by presence of comorbid mental disorders.